(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
A tridactyl footprint referable to a theropod dinosaur, found on a limestone block of Late Hauterivian age, is described here. The block was used to build the pier of Porto Corsini (Ravenna, Italy); the site of provenance is located on the southern flank of the Cansiglio Plateau (Pordenone, Northeastern ltaly) where there are several quarries. This is the first record of a dinosaur footprint in the Cretaceous of Italy and the first indication of Hauterivian dinosaur tracks in the Periadriatic carbonate platforms.